Petrogenesis of Continental Intraplate Alkaline Basalts in the Tuoyun Basin, Western Central Asian Orogenic Belt: Implications for Deep Carbon Recycling - Cheng, Zhiguo; Zhang, Zhaochong; Wang, Zhenchao; Jin, Ziliang; Hao, Jinhua; Jin, Lei; Santosh, M (Journal of petrology, 2022)
Abstract The origin of intraplate volcanic provinces in continental interiors remains equivocal. One of the major gaps is the absence of a clear understanding of thermal state and the role of recycled carbon. Here we present results from detailed temperature estimation, trace element content of olivine and integrated Sr-Nd-O-Mg-Zn isotopic studies on Meso-Cenozoic basalt and basanite from the Tuoyun Basin in the western Central Asian Orogenic Belt. The calculated crystallization temperatures are in the range of 1101°C–1273°C for basalt and 1037°C–1295°C for basanite, consistent with ambient upper mantle-derived melts. Olivine Zn/Fe, Mn/Zn and Fe/Mn ratios fall in the hybrid source region composed of peridotite and pyroxenite for both basalt and basanite, which is also in agreement with their bulk-rock CaO-MgO trends, FeO/MnO ratios (62.8–77.4 for basalt, 57.8–65.1 for basanite) and FCKANTMS values (overall major element compositions; 0.52–0.68 for basalt, 0.43–0.64 for basanite). Trace elemental modeling shows that the basalt was produced by higher degrees of partial melting with more pyroxenite contribution than basanite. Mg and Zn isotopes show lighter Mg (−0.45 to −0.55‰ for basalt, −0.45 to −0.47‰ for basanite) and heavier Zn (0.37–0.41‰ for basalt, 0.38–0.48‰ for basanite) isotopic compositions than primitive mantle, indicating the possible involvement of recycled sedimentary carbonate in mantle source. Conversely, the basalt and basanite lack typical ‘carbonatitic fingerprints’ such as high CaO/Al2O3 ratios and negative Zr, Hf and Ti anomalies. Furthermore, the Sr-O isotopes display typical mantle affinity without explicit crustal signatures. Such a decoupling is attributed to carbonate species transition and decarbonation reactions between carbonate and surrounding silicate during plate subduction at a depth of >150 km where the following reactions take place: CaMg(CO3)2 (dolomite) = MgSiO3 (magnesite) + CaCO3 (aragonite) and MgCO3 (magnesite) + SiO2 (coesite) → MgSiO3 (enstatite) + CO2. When the recycled carbonates are exhausted, crustal Sr-O is released but the Mg-Zn isotopic anomalies are inherited by the silicate products (‘ghost carbonate’). These silicates are expected to be involved in the subsequent mantle upwelling that induces decompression melting to generate intraplate magmas. We therefore propose recycled carbonates in the mantle sources of the Tuoyun lavas that underwent recycling at depths >150 km were incorporated as ‘ghost carbonate’ with recycled Mg and Zn elements in the partial melting process rather than directly in the carbonate form.